Pembiayaan Pendidikan Berbasis Filantropi Islam: Strategi Rumah Pintar BAZNAS Piyungan Yogyakarta - Sauqi Futaqi; Imam Machali (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2018)
This study aims to investigate the financial management and strategies deployed by Rumah Pintar (Rumpin) BAZNAS Piyungan Bantul Yogyakarta to improve the quality of education. Employing a qualitative approach, the data of this research is collected through observation, interviews, and documentation. The data were then analyzed in three stages: data reduction, data display and data verification. The results show that financial resources of Rumpin BAZNAS Piyungan are obtained from zakat through BAZNAS Center and through the allocation of costs in Rumpin that has increased from year to year. The improved allocation of costs were caused by the increasing need for services requested by the service recipients (mustahik). The result of the cost improvement is the increasing quality of education and services. It can be seen from the achievements obtained by Rumpin BAZNAS Piyungan which won number of awards such as the Best Rumpin in center development under the category of Non-Departmental body; received award of pustaka bakti tama penggerak buku (books reader movement for literary devotion) and several training certificates that can be used to find a job.